Las nuevas embajadas en Berlín - Tetzlaff, Patricia (1999)
Proyecto Once, Rem Koolhaas, Paises Bajos; Proyecto Hans Hollein, Austria; Proyecto Gonzalez de León Solano, México; Proyecto Wilford, Gran Bretaña
Keywords: EMBAJADAS; ALEMANIA; BERLIN; ECOLOGIA; HOLLEIN, HANS; WILFORD, MICHAEL; GONZALEZ DE LEON, TEODORO; SOLANO, FRANCISCO